2018
DOI: 10.1111/cpf.12539
|View full text |Cite
|
Sign up to set email alerts
|

Low skeletal muscle mass is associated with low aerobic capacity and increased mortality risk in patients with coronary heart disease – a CARE CR study

Abstract: Skeletal muscle mass was positively correlated with O in patients with CHD. Peak oxygen pulse had the strongest association with SMM. Low ASM% was associated with a higher risk of all-cause mortality. The effects of exercise and nutritional strategies aimed at improving SMM and function in CHD patients should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 44 publications
(80 reference statements)
2
47
0
1
Order By: Relevance
“…In contrast, exercise rehabilitation may reduce sympathetic activity and improve HF outcomes by its effect on muscle function. It has been demonstrated that low skeletal muscle mass is associated with low aerobic capacity and increased mortality risk in HF patients (CARE-CR study) [63].…”
Section: Sarcopenia Ergoreflex and Hfmentioning
confidence: 99%
“…In contrast, exercise rehabilitation may reduce sympathetic activity and improve HF outcomes by its effect on muscle function. It has been demonstrated that low skeletal muscle mass is associated with low aerobic capacity and increased mortality risk in HF patients (CARE-CR study) [63].…”
Section: Sarcopenia Ergoreflex and Hfmentioning
confidence: 99%
“…Similarly, exercise may induce left ventricular dysfunction which can also limit peak stroke volume and therefore, Q [55]. These factors may impede the delivery of oxygenated blood to the exercising muscle [56,57] where adverse changes to skeletal muscle physiology including low muscle mass [58,59], poor perfusion and matching of the capillaries and muscle fibres, as well as reduced muscle oxidative capacity [56], may reduce a-vO 2 diff and aerobic synthesis of adenosine triphosphate [55]. A low Q and a-vO 2 diff causes a marked reduction in VO 2peak such that the VO 2peak of men (20.2 ml • kg − 1 • min − 1 ) [51] and women (15.1 ml • kg − 1 • min − ) [52] with heart disease who are aged between 50 and 59 years is typically half of that found in healthy men (42.1 ml • kg − 1 • min − 1 ) and women (33.7 ml • kg − 1 • min − 1 ) of a similar age [60].…”
Section: The Role Of Aerobic Fitnessmentioning
confidence: 99%
“…In fact, physical fitness is considered one of the most important health markers and commonly understood as a predictor of morbidity and mortality for cardiovascular diseases [ 14 , 15 ]. As such, numerous studies have shown that a high BMI and/or obesity are associated with poor physical fitness due to the higher body fat and lower skeletal muscle mass [ 16 19 ]. Moreover, both skeletal muscle mass and strength might be closely associated with cardiorespiratory fitness [ 20 , 21 ] and health [ 22 ], providing reasoning to assume that skeletal muscle may mediate the relationship between NWO and physical fitness.…”
Section: Introductionmentioning
confidence: 99%